Записки охотника - Тургенев Иван Сергеевич (Внеклассное чтение, 2007)
Экземпляры: ф.8 (2008) / Инвентарный номер: 51983 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 87 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-4